Aromatic hydrocarbon biodegradation activates neutral lipid biosynthesis in oleaginous yeast. (May 2018) - Deeba, Farha; Pruthi, Vikas; Negi, Yuvraj S.
Graphical abstract: Highlights: Oleaginous yeast of Cryptococcus spps degrade wide range of AHs. AHs biodegradation activates accumulation of acetyl-CoA in the cytosol. AHs degradation end products act as precursors for de novo synthesis of lipid. Maximum lipid productivity (0.0444 g/L/h)was recorded on phenol (1 g/L) Biodiesel obtained depicts improved oxidative stability. Abstract: In this study, the biodegradation ability of oleaginous yeast Cryptococcus psychrotolerans IITRFD for aromatic hydrocarbons (AHs) was investigated. It was found to completely degrade range of AHs such as 1 g/L phenol, 0.75 g/L naphthalene, 0.50 g/L anthracene and 0.50 g/L pyrene with lipid productivity (g/L/h) of 0.0444, 0.0441, 0.0394 and 0.0383, respectively. This work demonstrated the ring cleavage pathways of AHs by this yeast which follow ortho route for phenol and naphthalene while meta route for anthracene and pyrene degradation. The end products generated during biodegradation of AHs are feed as precursors for de novo triacylglycerols (TAG) biosynthesis pathway of oleaginous yeast. A high quantity of lipid content (46.54%) was observed on phenol as compared to lipid content on naphthalene (46.38%), anthracene (44.97%) and pyrene (44.16%). The lipid profile revealed by GC–MS analysis shows elevated monounsaturated fatty acid (MUFA) content with improved biodiesel quality.